PERANAN GURU FIQIH DALAM MENINGKATKAN KETAATAN IBADAH SHALAT MTs AL IHSAN - Ahmad Farizal (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
Prayer worship is education and guidance provided by fiqh teachers to students, so that students understand the worship and its implementation in everyday life. that as creatures who are able to think properly and early baliq humans, they should have embedded self-awareness about their obligations to Allah SWT, namely worshiping him (prayer). The question in this study is how the role of the fiqh teacher in improving the observance of prayer at MTs Al-Ihsan Tanah Grogot. The purpose of this study was to determine the role of the fiqh teacher in improving the obedience of prayer at MTs Al-Ihsan Tanah Grogot. This research uses qualitative field research with descriptive research. This research uses data collection techniques with interviews, observation and documentation. Data validity techniques using triangulation of sources, techniques and time. Data analysis techniques use data reduction, data presentation then conclusions. The results of the study are as follows: The role of the Fiqh Teacher in improving the observance of prayer at MTs Al- Ihsan Tanah Grogot is said to be good. This can be seen from teachers who set an example by attending prayers together, familiarize by requiring students to pray together, enforce discipline by teaching prayers on time so as not to fall behind the next subject, motivate students by giving exemplary stories and giving advice, give gifts by giving additional grades and giving praise, punish by giving punishment in the form of cleaning the school bathroom and praying alone